JUDGEMENT, LEGAL ATTEMPT AND EXECUTION OF CRIMINAL LAW IN INDONESIA - Miftachur R Habibi (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
The judge's decision must be considered correct until there is a higher decision thatannuls it. The judge's decision must be based on the principles of real justice notmere procedural justice. the judge's decision must be based on the applicable laws and regulations. Sentencing, legal remedies and execution of criminal decisions have been stipulated in the Criminal Code (KUHP). In the implementation of execution against the defendant, supervision is carried out by the judge. This is to ensure that theimplementation is in accordance with the verdict and is carried out properly.